Шоколадный пес: [для среднего школьного возраста] / Холли Вебб ; перевод с английского Е. Солодянкиной - Вебб Холли (Эксмо, 2023)
Экземпляры: ДБ\СНО\10\12\27\28\29\30\31\32 (20240807) / Инвентарный номер: 67037 / Цена: 275.00 / Сис.шифр: И(англ)ср / Авт.знак: В 26 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)